The executive government of the Cape of Good Hope, 1825-54 - Fryer, Alan Kenneth (Rhodes University, Faculty of Humanities, Department of History, 1959)
The study of administrative processes is a relaltively new one both in the field of history and sociology. In both disciplines what is required is study of the sructure and growth of adminstrative systems and of the impact of administrative action on the community it seeks to serve and which it often provokes. In the field of history, Professor F. Tout in his chapters on administrative history ... gave new vitality and understanding to medieval studies. In the main, South African history, though probably not more so than other Commonwealth countries, has been less fortunate. Preface, p. 1.
Keywords: Cape of Good Hope (South Africa) -- History -- 1795-1872